Comparative effectiveness of natural and synthetic bone grafts in oral and maxillofacial surgery prior to insertion of dental implants: Systematic review and network meta-analysis of parallel and cluster randomized controlled trials. (May 2016) - Papageorgiou, Spyridon N.; Papageorgiou, Panagiotis N.; Deschner, James; Götz, Werner
Abstract: Objectives: Bone grafts are often used to enhance bone volume/quality prior to implantation insertion. This systematic review compares the histomorphometric effectiveness of bone grafts in an evidence-based manner. Data: Randomized clinical trials comparing histomorphometrically the % of newly-formed bone between two grafts were included. Risk of bias within and across studies was assessed with the Cochrane tool and the GRADE approach, respectively. Random-effects pairwise meta-analyses were conducted, followed by network meta-analysis, network meta-regression and sensitivity analyses. Sources: Four electronic databases were searched from inception to June 2015 without limitations. Study selection: A total of 12 trials (5 parallel; 7 cluster) with a total of 231 patients (302 grafted sites) were included. No statistically significant differences were found in the % of new bone from pairwise comparisons between any two bone grafts. Treatment ranking based on the evidence network indicated that autografts presented the highest percentage of new bone, followed by synthetic grafts, xenografts, and allografts. No differences according to patient age, sex, healing time, membrane used or kind of surgical graft use were identified. Our confidence on pairwise comparisons was moderate to very low due to study limitations, inconsistency, and imprecision; our confidence on graft ranking was moderate due to study limitations. Conclusions: No significant differences were found in the percentage of new bone between any two grafts. Clinical significance: Synthetic bone substitutes or xenologous bone grafts can be used as an alternative to autologous graft in order to overcome problems of additional surgeries or limited graft availability.